Performance of the ForenSeqTM DNA Signature Prep kit on highly degraded samples. Issue 8 (9th February 2017) - Fattorini, Paolo; Previderé, Carlo; Carboni, Ilaria; Marrubini, Giorgio; Sorçaburu‐Cigliero, Solange; Grignani, Pierangela; Bertoglio, Barbara; Vatta, Paolo; Ricci, Ugo
Abstract : Next generation sequencing (NGS) is the emerging technology in forensic genomics laboratories. It offers higher resolution to address most problems of human identification, greater efficiency and potential ability to interrogate very challenging forensic casework samples. In this study, a trial set of DNA samples was artificially degraded by progressive aqueous hydrolysis, and analyzed together with the corresponding unmodified DNA sample and control sample 2800 M, to test the performance and reliability of the ForenSeq TM DNA Signature Prep kit using the MiSeq Sequencer (Illumina). The results of replicate tests performed on the unmodified sample (1.0 ng) and on scalar dilutions (1.0, 0.5 and 0.1 ng) of the reference sample 2800 M showed the robustness and the reliability of the NGS approach even from sub‐optimal amounts of high quality DNA. The degraded samples showed a very limited number of reads/sample, from 2.9–10.2 folds lower than the ones reported for the less concentrated 2800 M DNA dilution (0.1 ng). In addition, it was impossible to assign up to 78.2% of the genotypes in the degraded samples as the software identified the corresponding loci as "low coverage" (< 50x). Amplification artifacts such as allelic imbalances, allele drop outs and a single allele drop in were also scored in the degraded samples. However, the ForenSeq TM DNA Sequencing kit, on the Illumina MiSeq, was able to generate data which led to the correct typing of 5.1–44.8% and 10.9–58.7% of 58 of the STRs and 92 SNPs, respectively. In all trial samples, the SNP markers showed higher chances to be typed correctly compared to the STRs. This NGS approach showed very promising results in terms of ability to recover genetic information from heavily degraded DNA samples for which the conventional PCR/CE approach gave no results. The frequency of genetic mistyping was very low, reaching the value of 1.4% for only one of the degraded samples. However, these results suggest that further validation studies and a definition of interpretation criteria for NGS data are needed before implementation of this technique in forensic genetics.